PENGEMBANGAN E-MODUL BERBASIS STEM PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT DI KELAS XI SMA METHODIST 8 MEDAN - Westy Natasya Sitorus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a STEM-based electronic module (E-Module) on electrolyte and non-electrolyte solution materials and to determine its feasibility, effectiveness, practicality, and students’ responses. The research employed the Research and Development (R&D) method using the 4D model consisting of Define, Design, Develop, and Disseminate stages. The study was conducted at SMA Swasta Methodist 8 Medan involving Grade XI students. Data collection instruments included validation sheets, practicality questionnaires, student response questionnaires, and critical thinking ability tests. The developed E-Module was validated by material experts and media experts before being implemented in learning activities. The results showed that the STEM-based E-Module was categorized as highly feasible with a material expert validation score of 89.78% and a media expert validation score of 87.00%. The effectiveness test indicated an increase in students’ critical thinking skills, as reflected by the average pretest score of 24.91 and posttest score of 78.69, with an N-Gain value of 0.716 in the high category. Student responses reached 88.28% with a very good category, while teacher practicality assessment reached 98.67% with a very practical category. These findings indicate that the STEM-based E-Module is feasible, effective, practical, and receives positive responses from users, making it suitable as a digital learning resource in chemistry learning, particularly on electrolyte and non-electrolyte solution materials.